Glass and stoneware knapped tools among hunter-gatherers in southern Patagonia and Tierra del Fuego - Nuevo Delaunay, Amalia (2017)
The European colonisation of South America had different effects on the indigenous peoples, particularly on mobile hunter-gatherer societies such as those that inhabited mainland southern continental Patagonia and the island of Tierra del Fuego. The combination of archaeological data with ethnographic and historical accounts shows contrasting contexts for the manufacture of scrapers and projectile points with new raw materials such as glass and stoneware within these two distinct geographic areas. These differences are explained by a number of key factors: The introduction of the horse, the role of guanaco in a newly imposed capitalist economic framework, demographic patterns, bio-geographic barriers and the establishment of 'reservations' and missions.